Agreement and disagreement in modern english discourse - Sabadokha Oleksandra (My University, 2024)
This work delves into the linguistic phenomena of agreement and disagreement in Modern English, highlighting their role in effective communication. The research examines the various grammatical and lexical means through which agreement and disagreement are expressed, contributing to a deeper and better understanding of language usage and interpersonal interactions. The practical aspect of the work is centered on classic books and movies, which serve as the prism, through which the concepts of agreement and disagreement will be explored. In the context of Modern English discourse, this study aims to offer an investigation of the language phenomena such as agreement and disagreement, clarifying their crucial role in fostering efficient communication. This work enhances the understanding of language dynamics and interpersonal interactions by examining the variety of grammatical, lexical and nonverbal mechanisms utilized in expressing agreement and disagreement. The focus of this research is on the books and films, which act as frameworks for an in-depth review of agreement and disagreement in a range of sociocultural situations. These works act as an integral part in clarifying the complex relationship between language and social dynamics, providing the comprehension into the intricacies of interpersonal communication. Furthermore, this study establishes an in-depth method, merging information from descriptive, sociolinguistic, corpus-based, and discourse analysis to ensure an accurate and complex inquiry into the intricate dynamics of agreement and disagreement in Modern English discourse.

Ця робота розглядає такі лінгвістичні поняття як згода і незгода в контексті сучасного англійського дискурсу та наголошує на їх важливості під час ефективного спілкування. В ній також представлені засоби, що виражають згоду та незгоду, та які сприяють кращому розумінню мови та міжособистісної комунікації. В роботі поняття згоди і незгоди досліджуються через запропоновані фільми та книжки. З огляду на сучасний англомовний дискурс, робота має на меті дослідити мовні явища згоди та незгоди та зʼясувати яку вони відіграють роль у комунікації. Розглядаючи різноманітні граматичні, лексичні та невербальні механізми, які використовуються для вираження згоди і незгоди, ця робота поглиблює розуміння мови, її динаміки та вплив на міжособистісне спілкування. Дане дослідження фокусується на обраних творах літератури та фільмах, що слугують підґрунтям для аналізу понять згоди і незгоди в різних соціокультурних умовах. Допоміжні матеріали в роботі дозволяють зрозуміти звʼязок між мовою та соціокультурним контекстом та забезпечують розуміння використання згоди і незгоди в міжособистісній комунікації. Отже, ця робота поєднує описовий, соціолінгвістичний, корпусний та дискурсивний аналіз, задля комплексного дослідження динаміки згоди і незгоди в сучасному англійському дискурсі.
Keywords: agreement; disagreement; communication; linguistic means; grammatical means; books; згода; комунікація; мовні засоби; граматичні засоби; фільми